(3hbGjI GdQhGjI aj eSGFd GdgOGjIs - (3HQgGf GdTQjYI , eMehO Hf YHjOGddg Hf EHQGgje GdeMHhHj GdMfaj,J (B673 (3g` s
(3ChdgG (B:s
(3MeO ef LYd GdYde CLd GdehGgH GdSfjI CMSf eG jaJJM Hg GdcdGe hHYO aEf GdhdO GdCYR YHjO Gddg deG aQZ ef MaX GdcJH GdCOHjI CMHHJ Cf jMaX ai Yde GdCMcGe cJGHkG QGHYkG hdYjhf eSGFd Gdabg QGYjkG s
(3BNQgG (B:s
(3hEdG adG , hai Zfe ePHhMI ajgG ejJI gi Cbd fMQi hBcd ai GdENJjGQ GdMeO ddg Ydi GdJeGe hGdUdGI Ydi SjO GdCfGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ eOGNd GdCHhGH HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B178 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B406s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B202s
Keywords: (3Gdabg GdESdGejs